Hindering the formation and promoting the dispersion of medical biofilms: non-lethal effects of seagrass extracts - Luca De Vincenti; Yvana Glasenapp; Cristina Cattò; Federica Villa; Francesca Cappitelli; Jutta Papenbrock (BMC, 2018)
Abstract Background Biofilms have great significance in healthcare-associated infections owing to their inherent tolerance and resistance to antimicrobial therapies. New approaches to prevent and treat unwanted biofilms are urgently required. To this end, three seagrass species (Enhalus acoroides, Halophila ovalis and Halodule pinifolia) collected in Vietnam and in India were investigated for their effects in mediating non-lethal interactions on sessile bacterial (Escherichia coli) and fungal (Candida albicans) cultures. The present study was focused on anti-biofilm activities of seagrass extracts, without killing cells. Methods Methanolic extracts were characterized, and major compounds were identified by MS/MS analysis. The antibiofilm properties of the seagrass extracts were tested at sub-lethal concentrations by using microtiter plate adhesion assay. The performance of the most promising extract was further investigated in elegant bioreactors to reproduce mature biofilms both at the solid/liquid and the solid/air interfaces. Dispersion and bioluminescent assays were carried out to decipher the mode of action of the bioactive extract. Results It was shown that up to 100 ppm of crude extracts did not adversely affect microbial growth, nor do they act as a carbon and energy source for the selected microorganisms. Seagrass extracts appear to be more effective in deterring microbial adhesion on hydrophobic surfaces than on hydrophilic. The results revealed that non-lethal concentrations of E. acoroides leaf extract: i) reduce bacterial and fungal coverage by 60.9 and 73.9%, respectively; ii) affect bacterial biofilm maturation and promote dispersion, up to 70%, in fungal biofilm; iii) increase luminescence in Vibrio harveyi by 25.8%. The characterization of methanolic extracts showed the unique profile of the E. acoroides leaf extract. Conclusions E. acoroides leaf extract proved to be the most promising extract among those tested. Indeed, the selected non-lethal concentrations of E. acoroides leaf extract were found to exert an antibiofilm effect on C. albicans and E. coli biofilm in the first phase of biofilm genesis, opening up the possibility of developing preventive strategies to hinder the adhesion of microbial cells to surfaces. The leaf extract also affected the dispersion and maturation steps in C. albicans and E. coli respectively, suggesting an important role in cell signaling processes.